A method of repairing a lead acid battery
By combining composite high- and low-frequency pulse resonance with a repair agent, lead sulfate crystals on lead-acid battery plates are removed, a protective layer is constructed, and the problems of battery performance degradation and resource waste are solved, achieving efficient battery repair and reuse.
Patent Information
- Application Number
- CN202611340877.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-09-01
AI Technical Summary
In existing technologies, lead-acid batteries suffer severe performance degradation after a certain number of years of use, making it difficult to meet usage requirements. Furthermore, waste battery resources are not effectively utilized, resulting in high costs and environmental problems.
A composite high- and low-frequency pulse resonance method is adopted, which combines sulfate, lipoic acid, diacid and polysaccharide derivative repair agents to remove lead sulfate crystals on the plate through resonance waves and build a protective layer on the plate surface to extend battery life.
The repaired battery can achieve 90-95% of the lifespan of a new battery, solving the problem of battery performance degradation, extending battery life, and enabling the reuse of waste batteries, avoiding the high costs and pollution caused by dismantling.
Smart Images

Figure CN122843563B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery repair technology, and in particular relates to a composite repair method for lead-acid batteries. Background Technology
[0002] In recent years, lead-acid batteries have demonstrated enormous potential in emerging markets. Particularly in areas with underdeveloped power infrastructure, demand is booming for backup power and small-scale energy storage. Furthermore, the rapid growth of the electric bicycle and tricycle markets has also created new opportunities. In the energy storage market, with the increase in installed renewable energy capacity, lead-acid batteries are showing increasing advantages in home and grid-side energy storage, especially in cost-sensitive and safety-critical scenarios.
[0003] As the lead-acid battery market grows year by year, these batteries all need to be scrapped after reaching their service life. Currently, the industry situation is that there are abundant upstream waste battery resources, but due to the lack of mature battery repair technology on the market, expired batteries can only be dismantled for lead smelting and battery remanufacturing, resulting in huge cost losses and environmental problems. At present, the main problem facing batteries is performance degradation. Based on electrochemical characteristics, after about 3 years of service, the effective capacity of lead-acid batteries usually decreases to less than 60% of the rated capacity, which is difficult to meet the backup power supply requirements of computer rooms, and faces a mandatory replacement cycle. The main reasons for degradation are as follows: 1. Plate sulfation: accounting for about 70%-90% of failures, it is the most important factor for capacity reduction; 2. Water loss: long-term overcharging or high temperature causes electrolyte evaporation, increasing internal resistance; 3. Positive plate softening: active material falls off, increasing the risk of internal short circuits; 4. Replacement cycle: the replacement cycle of lead-acid batteries is generally 5 years, which is shorter than other equipment; 5. Procurement cost: the number of batteries is large, and the direct procurement cost for replacement is high.
[0004] Therefore, finding better battery repair methods, extending battery service life, and enabling the reuse of used batteries are of great technical significance to the development of the industry. Summary of the Invention
[0005] To address the aforementioned problems, this application provides a composite repair method for lead-acid batteries.
[0006] This application provides a composite repair method for lead-acid batteries, including the following steps: 1) Visual inspection and battery classification: Visual inspection and electrical performance testing are performed on the batteries to be repaired. Qualified batteries with intact physical structures are selected and classified according to their initial state. 2) Battery repair: Add water or acid to the classified batteries to be repaired so that the specific gravity of the electrolyte meets the battery's factory specifications. Then add repair agent to the electrolyte and let it stand for a week before performing resonance repair. The repair agents include sulfates, lipoic acid, diacids, and polysaccharide derivatives; 3) Cyclic test: Perform a battery capacity test on the repaired battery to complete the repair work.
[0007] Furthermore, in step 2), the repair agent comprises the following raw materials by weight percentage: 25-45% sulfate, 15-30% lipoic acid, 5-15% diacid, and the balance being polysaccharide derivatives.
[0008] Furthermore, in step 2), the diacid is prepared by polycondensation reaction of diethylene glycol and chloroacetic acid under alkaline conditions.
[0009] Furthermore, in step 2), the polysaccharide derivative is prepared by acylation reaction of chitosan oligosaccharide and succinic anhydride.
[0010] Furthermore, the molecular chain of chitosan oligosaccharides is 600-1500 Da.
[0011] Furthermore, in step 2), the amount of repair agent added to the electrolyte is 0.35-1wt%.
[0012] Furthermore, in step 2), the sulfate is one or more of copper sulfate, zinc sulfate, and sodium sulfate.
[0013] Furthermore, in step 2), the resonance is a composite frequency wave, which includes a sine wave with a center frequency of 5kHz-20kHz and a low-frequency modulation wave with a frequency of 50Hz-200Hz.
[0014] Furthermore, in step 1), the electrical performance test is a tensile test, specifically: adding deionized water or dilute sulfuric acid to the battery to be repaired, charging it, and then performing a 100A high-current discharge test, recording the battery's voltage drop and discharge duration, and classifying it accordingly.
[0015] Furthermore, in step 3), the battery capacity test specifically involves 3 charge and 3 discharge cycles at a current of 50A.
[0016] Compared with the prior art, this application has the following beneficial effects: This application employs a composite high- and low-frequency pulse resonance to generate voltage / current change resonant waves from the positive and negative terminals. This rapidly breaks down and removes lead sulfate crystals on the electrode surface, turning them into tiny particles that redissolve in the electrolyte, achieving high repair efficiency. The repaired battery life can reach 90-95% or more of that of a new battery. Furthermore, the combined effect of thioctic acid and diacid coordination activation and resonant wave physical stripping promotes the removal of deep, dense sulfation crystals. In addition, while removing lead sulfate, an in-situ film formation using polysaccharide derivatives constructs a protective layer on the newly formed spongy lead surface, effectively resisting secondary corrosion from dissolved oxygen and impurities, improving the problem of rapid capacity decay after repair, and further extending the cycle life of the repaired battery. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of SEM testing of the plates of a certain group of batteries before and after repair, according to an embodiment of this application. Detailed Implementation
[0018] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0020] When using “including,” “having,” and “contains” as described herein, the intention is to cover non-exclusive inclusion, unless an explicit qualifying term such as “only,” “consisting of,” etc., is used, in which case another component may be added.
[0021] The terms "preferred," "more preferably," "better," and "even better" used in this application refer to embodiments of this application that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this application. That is, in this application, "preferred," "more preferably," "better," and "even better" are merely descriptions of implementations or embodiments with better effects, but do not constitute a limitation on the scope of protection of this application.
[0022] In this application, terms such as "further," "even more," and "particularly" are used for descriptive purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0023] In this application, "at least one" means one or more, such as one, two, or more. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layered" means at least two layers, such as two layers, three layers, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.
[0024] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0025] Unless otherwise specified, all steps in this application may be performed sequentially or randomly. For example, the method comprising steps (a) and (b) indicates that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc. Unless otherwise stated, singular terms may include plural forms and should not be construed as having a quantity of one.
[0026] In this application, "above" or "below" includes the stated number. For example, "below 1" includes 1.
[0027] In this application, room temperature refers to 0~40℃, including but not limited to 10~40℃, or further to 20~30℃.
[0028] The present application will be further illustrated by the following examples, but these examples do not limit the scope of the present application.
[0029] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this application, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. All reagents or instruments whose manufacturers are not specified are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description in this application, any prior art methods, equipment, and materials similar to or equivalent to those described, used, or made by the methods, equipment, and materials in the embodiments of this application may be used to implement this application.
[0030] Example The lead-acid battery composite repair method of this embodiment includes the following steps: 1) Appearance inspection and battery classification: Remove batteries with physical phenomena such as bulging, deformation, cracking, leakage, acid creep on the terminals, broken grids, and deformation, and select qualified batteries to be repaired. Take the batteries to be repaired and conduct a battery tensile test. Specifically, after assembling the batteries to be repaired, adding water, and charging them, conduct a 100A high-current battery tensile test and classify the batteries according to the test results. 2) Battery repair: Add water or acid to the classified batteries to be repaired so that the specific gravity of the electrolyte meets the battery's factory specifications. Then add 0.5wt% of the repair agent to the electrolyte. After standing for one week, perform resonance repair. Specifically, generate voltage / current change vibration waves from the positive and negative terminals to remove sulfuric acid crystals. The resonance wave power is 10kHz and the repair time is 24h. The repair agent comprises the following components by weight percentage: 35% sulfate, 25% lipoic acid, 10% diacid and 30% polysaccharide derivative; 3) Cyclic test: Charge and discharge the repaired battery 3 times with a 50A current to test the battery capacity. Ensure that during the battery repair process, factors such as current, voltage, temperature, and electrolyte specific gravity reach the optimal repair state and do not damage the battery structure. Once the repaired battery is confirmed, the repair work is complete.
[0031] The sulfate in question is zinc sulfate.
[0032] The diacid was prepared as follows: In a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, reflux condenser, and constant-pressure dropping funnel, 0.1 mol of diethylene glycol and 0.25 mol of chloroacetic acid were added. Under nitrogen protection and constant stirring, a concentrated alkaline solution of 0.5 mol of sodium hydroxide and 20 mL of ultrapure water was slowly added, controlling the addition rate to keep the system temperature below 60 °C. After the addition was complete, the mixture was heated to reflux temperature and reacted under reflux for 8 hours. After the reaction was completed, the mixture was cooled to room temperature, and the resulting precipitate was added to 100 mL of hot methanol. After stirring to dissolve, the mixture was filtered, and the filtrate was allowed to slowly evaporate to obtain a white solid.
[0033] The polysaccharide derivative was prepared by the following steps: 10 g of chitosan oligosaccharide was dissolved in a 1% (w / w) aqueous solution of acetic acid, and a solution of succinic anhydride dissolved in dimethyl sulfoxide was slowly added dropwise, controlling the molar ratio of succinic anhydride to chitosan amino groups to be 1.5:1. The mixture was stirred at 40 °C for 8 h. After the reaction was completed, the product was precipitated in acetone, filtered, and dialyzed with water to remove impurities. The final product was then freeze-dried.
[0034] Control group 1 The combined repair method for lead-acid batteries in this control group includes the following steps: 1) Appearance inspection and battery classification: Remove batteries with physical phenomena such as bulging, deformation, cracking, leakage, acid creep on the terminals, broken grids, and deformation, and select qualified batteries to be repaired. Take the batteries to be repaired and conduct a battery tensile test. Specifically, after assembling the batteries to be repaired, adding water, and charging them, conduct a 100A high-current battery tensile test and classify the batteries according to the test results. 2) Battery repair: Add water or acid to the sorted batteries to make the electrolyte specific gravity meet the battery factory specifications. After standing for a week, perform resonance repair. Specifically, generate voltage / current change vibration waves from the positive and negative terminals to remove sulfuric acid crystals. The resonance wave power is 10kHz and the repair time is 24 hours. 3) Cyclic test: Charge and discharge the repaired battery 3 times with a 50A current to test the battery capacity. Ensure that during the battery repair process, factors such as current, voltage, temperature, and electrolyte specific gravity reach the optimal repair state and do not damage the battery structure. Once the repaired battery is confirmed, the repair work is complete.
[0035] Control group 2 The combined repair method for lead-acid batteries in this control group includes the following steps: 1) Appearance inspection and battery classification: Remove batteries with physical phenomena such as bulging, deformation, cracking, leakage, acid creep on the terminals, broken grids, and deformation, and select qualified batteries to be repaired. Take the batteries to be repaired and conduct a battery tensile test. Specifically, after assembling the batteries to be repaired, adding water, and charging them, conduct a 100A high-current battery tensile test and classify the batteries according to the test results. 2) Battery repair: Add water or acid to the sorted batteries to be repaired so that the specific gravity of the electrolyte meets the battery's factory specifications. Then add 0.5wt% of the repair agent to the electrolyte. After standing for one week, perform resonance repair. Specifically, generate voltage / current change vibration waves from the positive and negative terminals to remove sulfuric acid crystals. The resonance wave power is 10kHz and the repair time is 24 hours. The repair agent comprises the following components by weight percentage: 55% sulfate and 45% lipoic acid; 3) Cyclic test: Charge and discharge the repaired battery 3 times with a 50A current to test the battery capacity. Ensure that during the battery repair process, factors such as current, voltage, temperature, and electrolyte specific gravity reach the optimal repair state and do not damage the battery structure. Once the repaired battery is confirmed, the repair work is complete.
[0036] The sulfate in question is zinc sulfate.
[0037] Control group 3 The combined repair method for lead-acid batteries in this control group includes the following steps: 1) Appearance inspection and battery classification: Remove batteries with physical phenomena such as bulging, deformation, cracking, leakage, acid creep on the terminals, broken grids, and deformation, and select qualified batteries to be repaired. Take the batteries to be repaired and conduct a battery tensile test. Specifically, after assembling the batteries to be repaired, adding water, and charging them, conduct a 100A high-current battery tensile test and classify the batteries according to the test results. 2) Battery repair: Add water or acid to the sorted batteries to be repaired so that the specific gravity of the electrolyte meets the battery's factory specifications. Then add 0.5wt% of the repair agent to the electrolyte. After standing for one week, perform resonance repair. Specifically, generate voltage / current change vibration waves from the positive and negative terminals to remove sulfuric acid crystals. The resonance wave power is 10kHz and the repair time is 24 hours. The repair agent comprises the following components by weight percentage: 45% sulfate, 25% lipoic acid, and 30% polysaccharide derivative; 3) Cyclic test: Charge and discharge the repaired battery 3 times with a 50A current to test the battery capacity. Ensure that during the battery repair process, factors such as current, voltage, temperature, and electrolyte specific gravity reach the optimal repair state and do not damage the battery structure. Once the repaired battery is confirmed, the repair work is complete.
[0038] The sulfate in question is zinc sulfate.
[0039] The polysaccharide derivative was prepared by the following steps: 10 g of chitosan oligosaccharide was dissolved in a 1% (w / w) aqueous solution of acetic acid, and a solution of succinic anhydride dissolved in dimethyl sulfoxide was slowly added dropwise, controlling the molar ratio of succinic anhydride to chitosan amino groups to be 1.5:1. The mixture was stirred at 40 °C for 8 h. After the reaction was completed, the product was precipitated in acetone, filtered, and dialyzed with water to remove impurities. The final product was then freeze-dried.
[0040] Control group 4 The combined repair method for lead-acid batteries in this control group includes the following steps: 1) Appearance inspection and battery classification: Remove batteries with physical phenomena such as bulging, deformation, cracking, leakage, acid creep on the terminals, broken grids, and deformation, and select qualified batteries to be repaired. Take the batteries to be repaired and conduct a battery tensile test. Specifically, after assembling the batteries to be repaired, adding water, and charging them, conduct a 100A high-current battery tensile test and classify the batteries according to the test results. 2) Battery repair: Add water or acid to the sorted batteries to be repaired so that the specific gravity of the electrolyte meets the battery's factory specifications. Then add 0.5wt% of the repair agent to the electrolyte. After standing for one week, perform resonance repair. Specifically, generate voltage / current change vibration waves from the positive and negative terminals to remove sulfuric acid crystals. The resonance wave power is 10kHz and the repair time is 24 hours. The repair agent comprises the following components by weight percentage: 45% sulfate, 35% lipoic acid, and 20% diacid; 3) Cyclic test: Charge and discharge the repaired battery 3 times with a 50A current to test the battery capacity. Ensure that during the battery repair process, factors such as current, voltage, temperature, and electrolyte specific gravity reach the optimal repair state and do not damage the battery structure. Once the repaired battery is confirmed, the repair work is complete.
[0041] The sulfate in question is zinc sulfate.
[0042] The diacid was prepared as follows: In a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, reflux condenser, and constant-pressure dropping funnel, 0.1 mol of diethylene glycol and 0.25 mol of chloroacetic acid were added. Under nitrogen protection and constant stirring, a concentrated alkaline solution of 0.5 mol of sodium hydroxide and 20 mL of ultrapure water was slowly added, controlling the addition rate to keep the system temperature below 60 °C. After the addition was complete, the mixture was heated to reflux temperature and reacted under reflux for 8 hours. After the reaction was completed, the mixture was cooled to room temperature, and the resulting precipitate was added to 100 mL of hot methanol. After stirring to dissolve, the mixture was filtered, and the filtrate was allowed to slowly evaporate to obtain a white solid.
[0043] Control group 5 The combined repair method for lead-acid batteries in this control group includes the following steps: 1) Appearance inspection and battery classification: Remove batteries with physical phenomena such as bulging, deformation, cracking, leakage, acid creep on the terminals, broken grids, and deformation, and select qualified batteries to be repaired. Take the batteries to be repaired and conduct a battery tensile test. Specifically, after assembling the batteries to be repaired, adding water, and charging them, conduct a 100A high-current battery tensile test and classify the batteries according to the test results. 2) Battery Repair: Add water or acid to the sorted batteries to make the electrolyte specific gravity meet the battery's factory specifications. Then add 0.5wt% zinc sulfate to the electrolyte. After standing for one week, perform charge-discharge repair. Specifically: 0.1C constant current charging: charging current is 0.1 * battery capacity A, voltage limit 2.5V / cell; 5 hours of discharge, discharge current is 0.2 * battery capacity A; repeat 5 charge-discharge cycles to complete the repair. 3) Cyclic test: Charge and discharge the repaired battery 3 times with a 50A current to test the battery capacity. Ensure that during the battery repair process, factors such as current, voltage, temperature, and electrolyte specific gravity reach the optimal repair state and do not damage the battery structure. Once the repaired battery is confirmed, the repair work is complete.
[0044] Performance testing 1. Take several used batteries of the Leoch brand with a factory capacity of 500AH, and repair them according to the repair methods of Example 1 and Control Group 1-5 respectively. After the repair is completed, test the performance comparison of the batteries before and after the repair. The test results are shown in Table 1.
[0045] Capacity calculation instructions: The formula for calculating battery capacity at different temperatures is: Actual capacity Ct = C25 × [1 + 0.008 × (t - 25)] Example: At 0℃, C0 = 500 × [1 + 0.008 × (-25)] = 400Ah, with a capacity loss of 20%, meaning that the standard capacity of a 2V 500AH battery is 400AH (40A discharge ≥ 10 hours).
[0046] Example: At 5℃, the core calculation process is: Ct = C25 × [1+0.008×(t-25)] = 500 × [1+0.008×(5-25)] = 420Ah, that is, the standard capacity of a 2V 500AH battery is 420AH (42A discharge ≥10 hours).
[0047] Table 1. Performance test data of batteries repaired by the repair methods in Examples 1-5 and Control Groups 1-5 2. Following the repair method described in the embodiment, the base station battery of a certain tower company and the battery of a certain communication base station were repaired. The performance comparison data before and after the repair are shown in Table 2 and Table 3.
[0048] Table 2. Repair data of a base station battery for a certain tower company using the repair method of the embodiment. Table 3. Repair data of a communication base station battery using the repair method of the embodiment. Table 4 Comparison of discharge cell voltage (V) data before and after battery repair using the repair method in the example. 3. SEM tests were performed on the plates of a certain group of batteries before and after repair in the example to observe the sulfation. The test results are as follows: Figure 1 As shown, Figure 1 The left side shows the product before repair. Figure 1 The image on the right shows the repaired version.
[0049] Analyze Tables 1-4 and Figure 1 As can be seen, the repair method of this application can effectively remove the sulfation crystallization phenomenon of battery plates, and can restore the waste battery to more than 95% of the capacity and charge and discharge performance of a new battery. The repair cycle is short, making it suitable for fields such as communication base stations and data center energy storage backup power. Furthermore, the repair method of this application does not disassemble the battery, does not have high-temperature evaporation, and does not generate secondary pollution during the repair process.
[0050] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A composite repair method for lead-acid batteries, characterized in that: Includes the following steps: 1) Appearance inspection and battery classification: Perform appearance inspection and electrical performance testing on the batteries to be repaired, screen out qualified batteries with intact physical structure, and classify them according to their initial state; 2) Battery repair: Add water or acid to the classified batteries to be repaired so that the specific gravity of the electrolyte meets the battery's factory specifications. Then add a repair agent to the electrolyte and let it stand for a week before performing resonance repair. The resonance is a composite frequency wave, which includes a sine wave with a center frequency of 5kHz-20kHz and a low-frequency modulation wave with a frequency of 50Hz-200Hz. The repair agent comprises sulfate, lipoic acid, diacid, and polysaccharide derivative; the diacid is prepared by polycondensation reaction of diethylene glycol and chloroacetic acid under alkaline conditions; the polysaccharide derivative is prepared by acylation reaction of chitosan oligosaccharide and succinic anhydride; 3) Cyclic test: Perform a battery capacity test on the repaired battery to complete the repair work.
2. The composite repair method for lead-acid batteries according to claim 1, characterized in that: In step 2), the repair agent comprises the following raw materials by weight percentage: 25-45% sulfate, 15-30% lipoic acid, 5-15% diacid, and the remainder being polysaccharide derivatives.
3. The composite repair method for lead-acid batteries according to claim 1, characterized in that: The molecular chain of the chitosan oligosaccharide is 600-1500 Da.
4. The composite repair method for lead-acid batteries according to claim 1, characterized in that: In step 2), the amount of repair agent added to the electrolyte is 0.35-1wt%.
5. The composite repair method for lead-acid batteries according to claim 1, characterized in that: In step 2), the sulfate is one or more of copper sulfate, zinc sulfate, and sodium sulfate.
6. The composite repair method for lead-acid batteries according to claim 1, characterized in that: In step 1), the electrical performance test is a tensile test, which specifically involves adding deionized water or dilute sulfuric acid to the battery to be repaired, charging it, and then performing a 100A high-current discharge test. The voltage drop and discharge duration of the battery are recorded, and the battery is classified accordingly.
7. The composite repair method for lead-acid batteries according to claim 1, characterized in that: In step 3), the battery capacity test specifically involves 3 charge and 3 discharge tests at a current of 50A.
Citation Information
Patent Citations
Lead-acid storage battery repairing activating agent and preparation method thereof
CN108598602A
Lead-acid storage battery off-line resonance pulse repair method
CN110444823A
